Comparative Analysis of Axial Bearing Capacity and Settlement of Bored Pile Foundations Based on N-SPT Data in the WK-Kampar Oil Tank Construction Project - Ines Harjanti Putri; Yustian Heri Suprapto (Asosiasi Dosen Muda Indonesia, 2025)
Oil tank construction requires a reliable foundation system to support structural loads and prevent excessive settlement. In the WK-Kampar project, bored pile foundations were used to transfer loads to deeper and more stable soil layers. Objective: This study aims to compare the axial bearing capacity and settlement of bored pile foundations with diameters of 0.4 m, 0.5 m, and 0.6 m based on N-SPT data. Method: This research used a quantitative descriptive-comparative approach. Secondary data were obtained from soil investigation and foundation planning documents. The Reese & O’Neill method was used to calculate bearing capacity, while the Vesic method was used to estimate settlement. Findings: The allowable bearing capacities of single piles with diameters of 0.4 m, 0.5 m, and 0.6 m were 173.7 kN, 233.5 kN, and 299.8 kN. The corresponding pile group capacities were 1301.2 kN, 1664.2 kN, and 2030.6 kN, with settlement values of 3.95 cm, 4.16 cm, and 4.67 cm. The 0.4 m diameter bored pile with nine piles can be considered the most efficient alternative if its group capacity exceeds the tank working load. Implications: The findings show that a smaller pile diameter may still be technically acceptable when bearing capacity and settlement requirements are satisfied. Originality: This study integrates single pile capacity, pile group capacity, and settlement analysis for an actual oil tank foundation project using N-SPT data.